Rogue States as Norm Entrepreneurs - Wunderlich, Carmen. author. (orcid)0000-0002-7584-1408 Link aut Link
XIV, 281 p.
Keywords: This book investigates whether so-called rogue states – assumed antagonists of a Western-liberal world order – could also act as norm entrepreneurs by championing the genesis and evolution of global norms. The author explores this issue by analyzing the arms control policies of the Islamic Republic of Iran. A comparison with the prototypical norm entrepreneur Sweden and the Democratic People’s Republic of North Korea – a notorious norm-breaker – reveals interesting insights for norm research: Apparently, norm entrepreneurship manifests itself in different degrees and phases of the norm life cycle. The finding that Iran indeed acts as a norm entrepreneur in some cases also sheds light on those factors that might account for the success or failure of norm advocacy. Lastly, the book offers a new perspective on “rogue states”, by not only regarding them as irrational antagonists of the current world order, but also as legitimate participants in a discourse on what the ruling order should look like. This book will appeal to scholars interested in critical norm research in international relations. “This book offers cutting-edge norm research, highlighting how norm-breakers can function as norm-makers." Maria Rost Rublee, Associate Professor of International Relations, Monash University (Australia) “So-called ‘rogue states’ are typically understood as norm breakers, but Carmen Wunderlich makes a persuasive conceptual case backed by empirical research that we need to consider the extent to which they are in fact norm entrepreneurs in their own right. In an era characterized by much concern over the status of liberal norms, this is a very timely study.” Richard Price, Department of Political Science, The University of British Columbia (Canada) "At a time when the world order is under pressure, this cutting-edge analysis of how dissatisfied states challenge existing globalnorms illuminates a topic crucial to understanding contemporary international relations." Nina Tannenwald, Director, Watson Institute for International and Public Affairs, Brown University (Rhode Island USA).